Social Norms, Higher-Order Beliefs and the Emperor's New Clothes - Zaki Wahhaj (University of Kent, School of Economics, 2012)
The use of social sanctions against behaviour which contradicts a set of informal rules is often an important element in the functioning of informal institutions in traditional societies. In the social sciences, sanctioning behaviour has often been explained in terms of the internalisation of norms that prescribe the sanctions (e.g. Parsons 1951) or the threat of new sanctions against those who do not follow sanctioning behaviour (e.g. Akerlof 1976). We propose an alternative mechanism for maintaining a credible threat of social sanctions, showing that even in a population where individuals have not internalised a set of social norms, do not believe that others have internalised them, do not believe that others believe that others have internalised these norms, etc., up to a finite nth order, collective participation in social sanctions against behaviour which contradict the norms is an equilibrium if such beliefs exist at higher orders. The equilibrium can persist even if beliefs change over time, as long as the norms are believed to have been internalised at some finite nth order. The framework shows how precisely beliefs must change for the equilibrium to unravel and social norms to evolve.
Keywords: D01; D02; D83; Z10; 330; social norms; higher-order belief; social sanctions; community enforcement; dynamics of norms; institutional change